Pengaruh Kreativitas Guru terhadap Motivasi Belajar Siswa di SMP-SMA Cambridge School, Surabaya - Rumiyati, Rumiyati; Medyawati, Medyawati; Hia, Meniati; Juanda, Juanda (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
This study aims to determine the effect of teacher creativity on the learning motivation of junior senior high school students in Cambridge School Surabaya. The method used a quantitative method which first carried out by testing the validity and reliability of the study, then normality test, the test variable X abd Y is completely normally distributed, with to test linearity to show results linearity. From the regression analysis, it is known that the calculated F value is 10.262 with a signicance level 0.002>0.05 which indicates that there is a directing variable of teacher creativity (X) on student’s learning motivation (Y). While the hypothesis testing is based on the calculation of the correlation coefficient2 (coefficient of determination) of 0.316 or 31.6%. Based on the results of the study, teacher creativity has a significant effect on the student learning motivation. This is evidenced by the acceptance of the results of hypothesis testing conducted by researchers. Therefore, in order to increase students’ learning motivation, teachers must be able to increase creativity in teaching.